Modulation of serines 17 and 24 in the LC3-interacting region of Bnip3 determines pro-survival mitophagy versus apoptosis - Zhu, Yanyan; Eils, Roland; Hamacher-Brady, Anne (The journal of biological chemistry, 2013)
BH3-only proteins integrate apoptosis and autophagy pathways, yet regulation and functional consequences of pathway cross-talk are not fully resolved. The BH3-only protein Bnip3 is an autophagy receptor that signals autophagic degradation of mitochondria (mitophagy) via interaction of its LC3-interacting region (LIR) with Atg8 proteins. Here we report that phosphorylation of serine residues 17 and 24 flanking the Bnip3 LIR promotes binding to specific Atg8 members LC3B and GATE-16. Using quantitative multispectral image-based flow cytometry, we demonstrate that enhancing Bnip3-Atg8 interactions via phosphorylation-mimicked LIR mutations increased mitochondrial sequestration, lysosomal delivery, and degradation. Importantly, mitochondria were targeted by mitophagy prior to cytochrome c release, resulting in reduced cellular cytochrome c release capacity. Intriguingly, pro-survival Bcl-xL positively regulated Bnip3 binding to LC3B, sequestration, and mitochondrial autophagy, further supporting an anti-apoptotic role for Bnip3-induced mitophagy. The ensemble of these results demonstrates that the phosphorylation state of the Bnip3 LIR signals either the induction of apoptosis or pro-survival mitophagy. Background: Bnip3 is both a pro-apoptotic BH3-only protein and a mitochondrial autophagy receptor. Results: Serine phosphorylation of the Bnip3 LC3-interacting region (LIR) increased binding to Atg8 members and consequently mitophagy, in a manner positively regulated by Bcl-xL. Conclusion: The Bnip3 LIR activity state determines either pro-survival mitophagy or mitochondrial apoptosis. Significance: Bnip3-induced mitophagy is serine kinase-regulated and thus a targetable pathway.
Elektronische Reproduktion der Druckausgabe
Gesehen am 28.07.2021